The absorption spectrum of ammonia between 5650 and 6350 cm−1. (January 2021) - Cacciani, P.; Čermák, P.; Béguier, S.; Campargue, A.
Highlights: An absorption spectrum of ammonia recorded at Kitt Peak in 1991 is analysed near 1.6 µm. The analysis uses combination difference relations and the C2018 variational line list. 2779 ammonia lines are measured in the 5650 - 6350 cm −1 region. 1762 lines are assigned to 29 bands providing 914 new experimental energy levels. The obtained data will be valuable to identify NH3 lines in the 1.6 µm atmospheric window. Abstract: A room temperature Fourier Transform absorption spectrum of ammonia measured in 1991 and available from the Kitt Peak data center is analyzed in the 5650 - 6350 cm −1 region. This spectral interval is part of the important 1.6 µm atmospheric transparency window where ammonia could be detected as trace species. The centers and intensities of 2779 ammonia lines were retrieved using a multiline fitting procedure. The spectrum was assigned by the joint use of a recent variational line list and of lower state combination difference relations. Overall, 1762 lines were assigned to 29 bands providing 914 new experimental energies. The obtained assignments and upper state experimental energies are the first for ammonia in the studied region. The comparison of our line list to the variational line list, to the HITRAN2016 list and to a very recent experimental line list is presented and discussed. Graphical abstract: Image, graphical abstract